Large single crystals of graphene on melted copper using chemical vapor deposition. - Wu, Y; Fan, Y; Speller, S; Creeth, G; Sadowski, J; He, K; Robertson, A; Allen, C; Warner, J (2012)
A simple method is presented for synthesizing large single crystal graphene domains on melted copper using atmospheric pressure chemical vapor deposition (CVD). This is achieved by performing the reaction above the melting point of copper (1090 °C) and using a molybdenum or tungsten support to prevent balling of the copper from dewetting. By controlling the amount of hydrogen during growth, individual single crystal domains of monolayer graphene greater than 200 μm are produced within a continuous film. Stopping growth before a complete film is formed reveals individual hexagonal domains of graphene that are epitaxially aligned in their orientation. Angular resolved photoemission spectroscopy is used to show that the graphene grown on copper exhibits a linear dispersion relationship and no sign of doping. HRTEM and electron diffraction reveal a uniform high quality crystalline atomic structure of monolayer graphene.